(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of a combination of intradialytic exercise and instrumental music therapy on reducing insomnia in patients with chronic renal failure. The method used was a pre-post quasi-experiment with an intervention group and a control group. The results showed that in the intervention group there was a difference in the pre and post insomnia index with a t value = 10.676 and a p value = 0.001. In the control group, there was no difference in the pre and post insomnia index with a t value = 0.900 and p = 0.381. There was a significant effect in the intervention group compared to the control group with a t value = 10.676 and a p value of 0.001 <0.05. In conclusion, there is an effect of a combination of intradialytic exercise and instrumental music therapy on reducing insomnia in patients with chronic renal failure. Keywords: Chronic Renal Failure, Insomnia, Intradialytic Exercise, Instrumental Music Therapy.